Interpretation of the prohibition on doing business in the field of forex trading for soldiers of the Indonesian National Army reviewed from Article 39 Number 3 of Law Number 34 of 2004 Concerning The Indonesian National Army - Haryadi Ismail (Goodwood Publishing, 2024)
Purpose: The purpose of this study is to analyze the interpretation of the prohibition on doing business in forex trading for TNI soldiers and the regulation of forex trading businesses that do not interfere with their main duties. Research methodology: The research method used is normative legal research with a descriptive analytical approach, examining relevant legal regulations, theories, and literature. Results: The results of the study indicate that the prohibition on doing business for TNI soldiers aims to maintain professionalism and prevent conflicts of interest. However, exceptions can be given for passive investments that do not interfere with main duties. In addition, regulations that include business definitions, strict supervision, financial education, and strict law enforcement are needed to ensure that involvement in forex trading does not interfere with the main duties of TNI soldiers.